2017
DOI: 10.1007/s12602-017-9313-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Synbiotic Supplementation on Pregnancy Outcomes in Gestational Diabetes

Abstract: Synbiotics are known to exert multiple beneficial effects, including anti-inflammatory and antioxidative actions. This study was designed to evaluate the effects of synbiotic administration on biomarkers of inflammation, oxidative stress, and pregnancy outcomes among gestational diabetic (GDM) women. This randomized, double-blind, placebo-controlled clinical trial was carried out among 60 subjects with GDM who were not on oral hypoglycemic agents. Patients were randomly assigned to consume either one synbiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 47 publications
0
58
0
Order By: Relevance
“…The 17 RCTs originated from China [ 48 , 49 ], Iran [ 39 , 40 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], and the USA [ 63 ] ( Table 2 ). Fourteen of the RCTs [ 39 , 40 , 48 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 62 ] were double blinded, and three were not [ 49 , 61 , 63 ]. Women were aged in their twenties [ 39 , 40 , 48 , 50 , 51 , 52 , 54 , 55 , 56 , 58 , 60 , 61 , 62 , 63 ] and thirties [ 53 , 57 , 59 ] in 13 and thre...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 17 RCTs originated from China [ 48 , 49 ], Iran [ 39 , 40 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], and the USA [ 63 ] ( Table 2 ). Fourteen of the RCTs [ 39 , 40 , 48 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 62 ] were double blinded, and three were not [ 49 , 61 , 63 ]. Women were aged in their twenties [ 39 , 40 , 48 , 50 , 51 , 52 , 54 , 55 , 56 , 58 , 60 , 61 , 62 , 63 ] and thirties [ 53 , 57 , 59 ] in 13 and thre...…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen of the RCTs [ 39 , 40 , 48 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 62 ] were double blinded, and three were not [ 49 , 61 , 63 ]. Women were aged in their twenties [ 39 , 40 , 48 , 50 , 51 , 52 , 54 , 55 , 56 , 58 , 60 , 61 , 62 , 63 ] and thirties [ 53 , 57 , 59 ] in 13 and three trials, respectively. Eleven trials included women with overweight and GDM [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 60 , 61 ], and five trials included women with obesity and GDM [ 39 , 40 , 48 , 59 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although numerous meta-analysis studies have focused on the influences of probiotic supplementation on the pregnant women’s metabolic profiles [ 39 , 40 , 41 , 42 ], none of them have emphasized its role in modifying microbiota alterations among pregnant women with GDM or obesity and its association with newborn birth weight. Studies on probiotic-based interventions in pregnant women have reported inconsistent results, whereas some studies have discovered borderline significant effects on birth weight [ 43 ]; other studies have reported the opposite result [ 44 ]. Moreover, these RCTs had limited sample sizes, making the pooling of summary results necessary.…”
Section: Introductionmentioning
confidence: 99%